2014
DOI: 10.1016/j.tdj.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated bleaching by low hydrogen peroxide regimens – with and without MI Paste Plus – on enamel hardness and composition

Abstract: Objectives: The aim of the present study was to test the following hypotheses: 1. In-vitro repeated bleaching by low hydrogen peroxide (HP) regimens eat 2-month interval-will affect enamel hardness and composition. 2. The use of MI Paste Plus, GC Co. (MIPP) during bleaching treatments will reduce these possible enamel changes. Methods: Two 14-day bleaching regimens; 1 h/day of 10% carbamide peroxide (CP) gel; Opalescence PF (OpPF) and 30 min/day of 9.5% HP strips; Crest Whitestrips Advanced Seal (CWAS) were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…This is in agreement with studies by Hala M Abass et al, Se abo hammar et al, Sule Bayrak et al, Asmaa Alkhtib et al [22][23][24][25] and can be due to the fact that the peptides in the CPP-ACP may diffuse into the inter-crystallite spaces, (as the size of the peptide complex is small [~2 nm]) created by bleaching. It localises and increases the bioavailability of calcium and phosphate ions and may enhance the potential for remineralization and deposition of minerals around the "freshly cleaned" enamel crystallites, leading to an increase in hardness thus regaining the prebleaching enamel physical properties.…”
Section: Methodssupporting
confidence: 91%
“…This is in agreement with studies by Hala M Abass et al, Se abo hammar et al, Sule Bayrak et al, Asmaa Alkhtib et al [22][23][24][25] and can be due to the fact that the peptides in the CPP-ACP may diffuse into the inter-crystallite spaces, (as the size of the peptide complex is small [~2 nm]) created by bleaching. It localises and increases the bioavailability of calcium and phosphate ions and may enhance the potential for remineralization and deposition of minerals around the "freshly cleaned" enamel crystallites, leading to an increase in hardness thus regaining the prebleaching enamel physical properties.…”
Section: Methodssupporting
confidence: 91%
“…On the other hand conversely, these results were in contrast with researches done by Abo-Hamar and Etman [33] found that bleaching with 10% carbamide peroxide 1h/day for 14 days or by 9.5% HP 30 min/day for 40 days didn't significantly decrease enamel VH and they explained that by Licensed Under Creative Commons Attribution CC BY it may be due to the balance between the demineralization and remineralization that was performed by artificial saliva.…”
Section: Discussioncontrasting
confidence: 71%
“…As pH 5.5 is slightly acidic, it can be the reason for dissolution of enamel and increased Ra. Some studies have reported that the pH of bleaching agent has a direct relationship with the surface roughness 36,37) . Acidic bleaching gels can demineralize the enamel and cause increase of surface roughness 36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the pH of bleaching agent has a direct relationship with the surface roughness 36,37) . Acidic bleaching gels can demineralize the enamel and cause increase of surface roughness 36,37) . Previous studies have revealed that 30-35% H2O2 can increase surface roughness and reduce the calcium-phosphorus ratio [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%